Persepsi Mahasiswa UNIMED Tentang Pembentukan Undang-Undang Kilat, Studi Kasus: (Undang-Undang Kontroversial Di Universitas Negara Medan) - Nuh Yabest Sinaga; Parlaungan Gabriel Siahaan; Novridah Reanti Purba; Muhammad Arif Siagian; Daffany Viroza; Anggie Pricyla Sianturi; Gita Mori Sevira Br Tarigan (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Fast-track legislation refers to a legislative process that proceeds rapidly, oftenwithout adequatepublic participation and is considered lacking in transparency.This study employs a descriptive qualitative method with data collection techniquesincluding observation, interviews, and documentation. The number of respondentsto be studied is approximately ten. The research focuses on one or more laws thatare considered controversial by the public, such as the Military Law (TNI Law), theJob Creation Law (Omnibus Law), and the Mineral and Coal Mining Law (MinerbaLaw). The aim of this study is to analyze the perceptions of Unimed students towardthe formation of fast-track legislation, particularly those that frequently sparkpublic controversy. This study aims to analyze the perceptions of Unimed studentsregarding the formation of fast-tracked legislation, particularly those that oftentrigger public controversy. The research is expected to provide an overview of theextent to which students understand, respond to, and critique the practice ofexpedited lawmaking, as well as highlight its impact on public trust in the legal drafting process in Indonesia. The findings indicate that the majority of UNIMEDstudents have a negative perception of fast-tracked legislation, as the process isconsidered rushed, lacks public participation, and does not follow a transparentdeliberative mechanism. The conclusion of this study is that the absence of publicinvolvement in the legislative process strengthens students' distrust in legislativeinstitutions, fosters a skeptical attitude, and even encourages their involvement incritical movements as a form of social control.